Who's your Mummy? - "Stine, R.L" (Scholastic: New Yark, 1993)
Abby and Peter pay a visit to their Uncle Jonathan, who seems very knowledgeable about Egyptian mummies, but they become suspicious at the strange sounds coming from a room inside his house, and their fears continue as they are invited to HorrorLand
Keywords: Horror fiction